Psychology of Health Quarantine Officers after a Year of the Covid-19 Pandemic - Semiani Semiani; Sri Wahyuni; Nopriadi Nopriadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The COVID-19 pandemic has an impact on the psychology of health quarantine officers if it cannot be handled, there is a chance for psychological distress to affect performance when carrying out their duties. This study aims to determine the psychological distress of health quarantine officers during the COVID-19 pandemic. This study uses a quantitative descriptive design. The research sample consisted of 111 respondents who were selected based on inclusion criteria using a total sampling technique. The data collection tool used is the Self Reporting Questionnaire (SRQ).Data were analyzed using univariate test. From research on 111 health quarantine officers, 104 people (93.7%) did not experience psychological distress. SRQ components in 7 respondents who indicated psychological distress showed symptoms of decreased energy 7 people (100%), cognitive symptoms 7 people (100%), anxiety symptoms6 people (85.7%), somatic symptoms 6 people (85.7%) and depression symptoms 3 people (42.9%). The majority of health quarantine officers are not indicated to be experiencing psychological distress. A person may have one or more types of indicators of psychological distress symptoms, the majority of the symptoms experienced by respondents are feeling a decrease in energy and cognitive symptoms